Spotlight on the manuscript of the letter of Sheikh Sayed Muhammad al-Khalif ibn al-Sheikh Syed al-Mukhtar al-Kunti to the children of Embark in the nineteenth century - Sidi M'hamed, Adab Ould (The Algerian Historical Journal, 2026)
The realization of manuscripts is considered the most important achievement for scholars and researchers in order to properly write the Arab-Islamic history in general and the Mauritanian history in particular, due to the abundance and diversity of manuscripts and the elimination of light on the ambiguous issues thereof, which requires preparing, revising and filtering them to make them accessible to everyone, including researchers and students, etc. The neglect of study and investigation Our manuscripts are an assassination of our deep cultural sentiments, especially the manuscripts that deal with the prevailing political situation at the time and are concerned with political reform and civil peace for tribal groups in the Sahara Desert. The text that we have investigated is from rare texts that are concerned with the political reality of tribal groups in the country of Chinguetti, and the manuscript letter falls within the framework of several letters of perseverance. The Kantian Zawiya sheikhs wanted to dedicate it and send it in order to reform, due to the characteristics of reform thought and their politics